An exploration of the health facility staff's perspectives on patients who disengage from HIV care: A qualitative analysis from Khayelitsha, Cape Town, South Africa - Nhemachena, Tsephiso (Department of Public Health and Family Medicine, 2022)
This project will be completed as a requirement for the Master of Public Health (MPH) degree at the University of Cape Town. This study is linked to an already existing project of Médecins Sans Frontières (MSF), which is called the Welcome Service. The Welcome Service focuses on addressing barriers that HIV+ patients face when they are returning to care after disengagement from treatment. One of the common barriers to re-engaging in treatment that the project seeks to address is the unwelcoming approach that health care workers have towards patients that disengage from treatment. To address this barrier the Welcome Service provides intervention through training packages for health care workers. The training packages seek to address staff behaviour that is unhelpful and unsupportive to patients that intend to reengage with treatment. The Welcome Service was initially implemented at Michael Mapongwana Clinic in Khayelitsha. This Clinic is in a peri-urban settlement in the Western Cape province of South Africa. This was then scaled up to Ubuntu Clinic, also in the same location. To measure the change in the Welcome service project, baseline semi-structured interviews with health facility staff at Ubuntu Clinic were conducted. Health facility staff that were interviewed at baseline will participate in an in-depth interview as a follow-up after attending Welcome Service training. As an MPH project, I will conduct secondary data analysis from baseline interviews of health facility staff at Ubuntu Clinic. The analysis will focus on interviews in which the perceptions and attitudes of health facility staff towards patients who disengage from treatment were gathered. These interviews may also explore health facility staff's perspectives on the reasons for patients disengaging from HIV treatment and reasons that might help patients to reengage with HIV treatment. This current project seeks to address the research question: What are the perspectives of health facilities staff on patients who disengage from HIV care in Khayelitsha, Cape Town, South Africa. This study will use inductive thematic analysis and the analysis will be done in NVivo, a qualitative data management software program. The researcher will identify themes from the trancripts and will not use a predetermined theory to derive themes, but will allow the data to guide theme development. Interviews were conducted by the MSF research team in English. The participants included in the study were doctors, nurses, counsellors, data clerks, security guards, and allied health professionals at Ubuntu Clinic. The respondents were above eighteen years old and were in the capacity to give consent on their own. The MSF research team was responsible for the recruitment of participants. All health facility staff that participated in this study were requested to give written informed consent to participate in the interviews. The findings of the primary study have not been published yet because the project is still in progress. The researcher received the questionnaire that was used in the study and from there the researcher developed a research question for this project. Some of the questions from the questionnaire asked the health facility staff if they feel able to deal with patients who disengage and how they feel when dealing with a patient who is returning to care. A data-sharing agreement was signed by the researcher and MSF before the researcher received the data obtained from MSF's project. The researcher will have access to the transcripts of the interviews, which have already been transcribed. In reporting, the researcher will not include the participants' names or any identifying information to ensure anonymity and confidentiality. This analysis aims to inform current and future health interventions to re-engage people living with HIV (PLWHIV) who have disengaged from care.